Relationships between morphological udder characteristics in Improved Valachian, Tsigai and Lacaune dairy sheep breeds - MAKOVICKÝ, PAVOL; MILERSKI, MICHAL; MARGETÍN, MILAN; MAKOVICKY, PETER; NAGY, MELINDA (The Indian Journal of Animal Sciences, 2019)
Udder morphology traits were measured and subjectively assessed by the use of linear scores and cistern cross-section areas were scanned by ultrasound machine, and were examined in 266 dairy ewes of Tsigai (TS), Improved Valachian (IV) and Lacaune (LC) dairy ewes. Measurements were recorded repeatedly within and between lactations, therefore 772 sets of measurements were collected in total. Analysis of variance was conducted with the mixed procedure of SAS statistical package. The model included effects of experimental day, parity, day in milk, random effect of animal and residual error. Subsequently correlations between random animal effects for udder measurements and linear scores were computed. Subjectively assessed linear scores for udder depth, cistern depth, teat angle and teat size showed high correlations with actual measurements of appropriate traits on udder in all examined breeds (rp=0.65–0.80).